Review on Methyl Ester Production from Inedible Rubber Seed Oil under Various Catalysts - Siti Norhafiza, Mohd Khazaai; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; M. M., Yusoff; Matsumura, Yukihiko (Elsevier Ltd, 2017)
The outcomes of the United Nations Climate Change Conference in Paris Convention (COP 21), the steady escalating of global carbon dioxide (CO2) concentration and the declaration of 2015 as the warmest year ever, demanding solutions to keep the earth fit for human habitation for years to come. One of such solutions is the use of biodiesel as an energy supply for diesel engines, that is regarded as a less environment-damaging fuel. As such, this review presents the possibility of utilizing non-edible rubber seed (Hevea brasiliensis) oil as a potential feedstock in biodiesel preparation via both homogeneous and heterogeneous acid and alkali catalysts. It deliberates the one-step and two-step routes of methyl ester production with various reaction conditions that to be weighted in order to achieve environment-responsibility yet cost-effective renewable fuel.